Diseño del plan de marketing turístico, mediante la aplicación de la metodología PIMTE 2014, para promover y fomentar el turismo en la laguna Julio Marin, ubicada en la Parroquia Nueva Loja, Cantón Lago Agrio, Provincia de Sucumbíos - Villalba Cando, Sandra Magali (2018)
The theme of this thesis work is: "DESIGN OF THE TOURIST MARKETING PLAN, THROUGH THE APPLICATION OF THE PIMTE 2014 METHODOLOGY, TO PROMOTE AND PROMOTE TOURISM AT LA LAGUNA JULIO MARIN, LOCATED IN THE NUEVA LOJA PARISH, CANTÓN LAGO AGRIO, PROVINCE DE SUCUMBÍOS. ", The objective of this work was to propose a Marketing Plan design, through the application of the methodology for Pimte 2014, to promote and promote tourism in the lagoon Julio Marín, located in the Nueva Loja parish, Lake Canton Agrio, province of Sucumbíos. The materials and methods used in the research, covers everything related to methods and techniques of study, being one of its foundations the foundations for sampling distribution, in order to apply a survey, the same that through their responses gave us favorable acceptance to the development of the present project. We proceeded to make a situational diagnosis considering the external analysis, where reference is made to the factors that affect the development of the activities of the Laguna Julio Marín, determining the Opportunities and Threats, likewise the Internal analysis was carried out, which allowed to determine the strengths and weaknesses, and based on the high impact matrix, determine the strategic objectives and propose the action plans that will allow the positioning of the Julio Marín Lagoon in the market. The proposal presented, establishes guidelines for a responsible, sustainable and sustainable tourism, not only linked to a consequence of applying the Marketing Plan, but also the conservation of the natural wealth and heritage of the locality, thus strengthening and promoting local tourism